Variations In Values Of Proximate Analysis In Aerva Lanata Juss Ex Schultes, Hedyotis Corymbosa (L.) Lam. And Leptadenia Reticulata (Retz.) W. & A. - MAMMEN D; DANIEL M; SANE RT (International Journal of Pharma and Bio Sciences, 2010)
Quality control methods are of utmost importance for maintenance of quality of herbal medicines. Literature values are available for a number of medicinal plants. Such values are considered to be standard and at times taken for granted. The present work was carried out to determine if the values of proximate analysis are consistent even with change of season or region of collection. If the values vary, then it is of utmost importance to determine the best time and place of collection for the plant. The various parameters studied were ash analysis, extractive values and moisture content for three plants Aerva lanata, Hedyotis corymbosa and Leptadenia reticulata. Each plant was collected during summer, monsoon and winter to study the effect of change of season on the proximate analysis values. Similarly the analysis was carried out for samples collected from Gujarat, Maharashtra and Kerala, to study the effect of geographical variation in the plants. Interestingly, the values were found to be change with season and region of collection of these plants.